Teleology and Structural Directedness - Nelson, Craig M. (2019)
This paper examines the argument that scientific thinkers who embrace a religious tradition can promote intellectual integration between religion and science rather than fragmented discourse. It is argued that God's Word as an event and the concept of structural directedness, an organized movement toward a future that does not demand a consciously intended end, may be helpful in understanding God's actions in an indeterminant way.